21 bridges [videorecording (DVD)] - Boseman, Chadwick; Miller, Sienna, 1981-; Kitsch, Taylor, 1981-; Carr, Gary, 1986- (Universal, 2020)
An embattled NYPD detective is thrust into a citywide manhunt for a pair of cop killers after uncovering a massive and unexpected conspiracy. As the night unfolds, lines become blurred on whom he is pursuing, and who is in pursuit of him. When the search intensifies, extreme measures are taken to prevent the killers from escaping Manhattan as the authorities close all of the city's bridges to prevent any entry or exit from the iconic island.